BIOKONVERSI LIMBAH ORGANIK SEBAGAI MEDIA BUDIDAYA MAGGOT BSF (Black Soldier Fly) GUNA MENINGKATKAN PEREKONOMIAN MASYARAKAT NAGARI TARAM - Kumbara; Ibnusina, Fedri; Shopia, Ikka Ade; Nofria, Rahma; Ilahi, Rendi Kurnia; Angela, Elsa; Afendo, Shafira Saumi; Lubis, Naimatul Ardhiah; Julnaidi (Green Engineering Society, 2023)
Organic waste is a serious problem in the Nagari Taram area, Limapuluh Kota Regency, West Sumatra Province, so it is necessary to bioconvert organic waste into valuable goods. The organic waste bioconversion program aims to reduce waste generation while providing additional income to the community. The implementation method is carried out by demonstration so that partner communities can more easily carry out organic waste bioconversion practices. In this program, BSF maggots are used to decompose household waste and restaurant waste. The maggots produced can be used as animal feed, especially for poultry farming and fishing, which are the jobs of the majority of people in Nagari Taram. Maggot harvesting also produces a by-product in the form of cassava, which can be used as organic fertilizer. This program provides education to local communities about the economic potential of organic waste management and BSF maggot cultivation techniques. The results of this program show that BSF maggots have a high protein content, making them suitable as animal feed. Apart from that, the cassava produced also has benefits as an organic fertilizer. This program provides ideas and motivation to the community to develop their own agricultural, livestock and fisheries businesses using resources originating from BSF maggots, thereby improving the standard of living of the people of Nagari Taram